PEMETAAN PEMASARAN KERELASIAN PELANGGAN, KOLABORASI PEMASOK, SUMBER DAYA PERUSAHAAN, KEUNGGULAN BERSAING DAN KINERJA PEMASARAN - hamzah, hamir (Badan Pengkajian dan Penerapan Teknologi, 2011)
To find out the cause of poor performance of SMEs metal automotive components in Java, author mapping “Customer Relationship Marketing, Suppliers Collaboration, Firm Resources, Competitive Advantage, Performance Marketing (a survey of SMEs metal automotive components in Java).